The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1002/chi.851
|View full text |Cite
|
Sign up to set email alerts
|

The caring child: an evaluative case study of the Cornwall Young Carers project

Abstract: This paper reports on an evaluation of the Cornwall Young Carers project (jointly funded by social services and the Cornwall and Isles of Scilly Health Action Zone), conducted during the period 2000–2002. A diverse range of methodological approaches were adopted (comparative national statistics, local pilot study, monthly and quarterly data capturing instruments, and a service user focus group) in monitoring and evaluating the project's high level statements/outcomes. Four evaluative themes are discussed, name… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 4 publications
2
34
0
Order By: Relevance
“…Similarly, in the United Kingdom, Butler and Astbury (2005) found that inappropriate levels of government income support, in proportion to the amount of caring they performed, often made young carers feel that recognition, praise or respect for their contribution was lacking. Young carers felt the strain of having to contribute to the family's finances and, in some cases, felt responsible for paying the mortgage and the household bills because existing financial support for their parents was inadequate.…”
Section: Financial Impactsmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, in the United Kingdom, Butler and Astbury (2005) found that inappropriate levels of government income support, in proportion to the amount of caring they performed, often made young carers feel that recognition, praise or respect for their contribution was lacking. Young carers felt the strain of having to contribute to the family's finances and, in some cases, felt responsible for paying the mortgage and the household bills because existing financial support for their parents was inadequate.…”
Section: Financial Impactsmentioning
confidence: 99%
“…In the United Kingdom, Butler and Astbury (2005) found that isolation, social exclusion and stigmatisation were major issues for young carers. Young carers reported that their role as carer restricted opportunities to socialise with their peers and resulted in carers having to 'steal' an hour here or there for social activities.…”
Section: Social Exclusion and Isolationmentioning
confidence: 99%
See 2 more Smart Citations
“…The general view is that YCs are negatively affected by the care situation, particularly in cases where the situation is long-term [4] and the child or young person has no healthy adults to turn to and rely on [5]. Young carers are at risk of becoming isolated and socially excluded and experiencing problems with school [6]. They may have to restrict their leisure time, leading to difficulty in maintaining friendships [6].…”
Section: Introductionmentioning
confidence: 99%